An overview of new design techniques for high performance CMOS millimeter-wave circuits - Ma, Shunli (2015)
CMOS millimeter-wave integrated circuits are more attractive due to its potential in higher integration with digitalsignal processing blocks and lower cost, compared to SiGe and GaAs. Meanwhile, the cut-off (ft) frequency of MOSFETs is continuously increased along with the scaling down of transistors as predicted with Moore's law. However, CMOS process suffers from high substrate loss and low quality (Q) of passive devices. As a result, circuit performance is hindered with degraded main block such as VCO, divider and LNA. In this paper, some new structures, such as meta-material oscillator, tunable inductors and coupled oscillator, are summarized and demonstrated to overcome these problems in designing high performance millmeter-wave circuits in nano-CMOS.